Composite current collector, composite pole piece, lithium battery and preparation method

By introducing a crosslinking layer into the composite fluid, crosslinking polymerization reaction is carried out using crosslinking agent, stabilizer and photoinitiator, the problem of low adhesion between the composite fluid is solved, and higher thermal stability and resistance are achieved Tensile strength improves the performance of lithium batteries.

CN119447213APending Publication Date: 2025-02-14ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410443320.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2024-04-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The adhesion between the existing composite fluid collecting layers is low and unstable, and there is a risk of easy peeling or falling off when heated, which affects the energy density and performance of the battery.

Method used

The structure of a polymer composite layer and a conductive layer is adopted, wherein the crosslinking layer is obtained by crosslinking polymerization reaction from a crosslinking agent, a stabilizer and a photoinitiator to enhance the thermal stability of the polymer substrate and improve the conductive layer and the polymer substrate. The bonding force between the films.

Benefits of technology

The thermal stability and tensile strength of the composite fluid collector are improved, the bonding force between the polymer substrate and the conductive layer is enhanced, and the risk of peeling is reduced, thereby improving the performance and service life of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447213A_ABST
    Figure CN119447213A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector, a composite pole piece, a lithium battery and a preparation method, the composite current collector comprises a polymer composite layer and a conductive layer, the conductive layer is located on at least one side of the polymer composite layer, the polymer composite layer comprises a polymer substrate and a cross-linking layer, the cross-linking layer is generated by coating at least one surface of the polymer substrate with a cross-linking polymer, the cross-linking layer is located between the conductive layer and the polymer substrate, and the cross-linking layer is used for enhancing the thermal stability of the polymer substrate; wherein the cross-linked polymer is at least obtained by a cross-linking polymerization reaction of a cross-linking agent, a stabilizer and a photoinitiator, the cross-linking agent is used for enhancing the binding force between the conductive layer and the polymer substrate, the stabilizer comprises at least two reactants, and the stabilizer is used for enhancing the thermal stability of the polymer substrate after the reaction.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to Chinese Patent Application No. 202310986901.1 filed in China on August 7, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present disclosure relates to the field of batteries, and in particular to a composite current collector, a composite pole piece, a lithium battery and a preparation method thereof. Background Art

[0005] The current collector is one of the important components of lithium-ion batteries. Its function is to carry active materials, collect and conduct electrons. An ideal lithium-ion battery current collector should meet the following characteristics: high electrical conductivity, good chemical and electrochemical stability, high mechanical strength, good compatibility and binding force with electrode active materials, low cost and easy availability, and light weight. Traditional current collectors generally use aluminum foil as the positive electrode current collector and copper foil as the negative electrode current collector. However, copper foil and aluminum foil are difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, people have developed composite current collectors. Compared with traditional metal foils, composite current collectors have the advantages of high conductivity, low cost, and light weight.

[0006] However, the existing composite current collectors have low and unstable adhesion between layers, and there is a risk of easy peeling or falling off when exposed to heat, which in turn affects the energy density and performance of the battery. Summary of the invention

[0007] In view of the above technical problems, the present disclosure provides a composite current collector, a composite pole piece, a lithium battery and a preparation method to solve or at least alleviate at least one technical problem existing in the above composite current collector, composite pole piece and lithium battery.

[0008] According to a specific embodiment of the present disclosure, the present disclosure provides a composite current collector, comprising a polymer composite layer and a conductive layer, wherein the conductive layer is located on at least one side of the polymer composite layer.

[0009] The polymer composite layer comprises a polymer substrate and a cross-linked layer, wherein the cross-linked layer is formed by coating a cross-linked polymer on at least one surface of the polymer substrate, and the cross-linked layer is located between the conductive layer and the polymer substrate, and the cross-linked layer is used to enhance the thermal stability of the polymer substrate;

[0010] The cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a stabilizer and a photoinitiator. The cross-linking agent is used to enhance the bonding force between the conductive layer and the polymer substrate. The stabilizer includes at least two types of reactants and is used to enhance the thermal stability of the polymer substrate after the reaction.

[0011] In some embodiments, the stabilizer includes: acrylic acid or acrylic acid derivatives, and isocyanate or isocyanate derivatives, wherein the reactant of isocyanate or isocyanate derivatives and the crosslinking agent is used to enhance the thermal stability of the polymer substrate.

[0012] In some embodiments, the stabilizer accounts for 1%-10% by weight of the cross-linked polymer.

[0013] In some embodiments, the acrylic acid or acrylic acid derivatives account for 0.5%-5% of the cross-linked polymer by weight; and the isocyanate or isocyanate derivatives account for 0.5%-5% of the cross-linked polymer by weight.

[0014] In some embodiments, the cross-linking agent comprises at least one of the following: methylenesuccinic acid, citraconic acid, mesaconic acid, 2-methylenesuccinic acid, succinic acid.

[0015] In some embodiments, the cross-linking agent accounts for 1%-5% by weight of the cross-linked polymer.

[0016] In some embodiments, the photoinitiator includes at least one of the following: diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, methyl benzoylformate.

[0017] In some embodiments, the mass percentage of the photoinitiator to the crosslinker is 1%-5%.

[0018] In some embodiments, the thickness of the polymer composite layer is 2.1-13 μm, wherein the thickness of the polymer substrate is 2-12 μm, and the thickness of the cross-linked layer is 0.1-1 μm.

[0019] In some embodiments, the conductive layer includes a conductive material layer and a transition layer, wherein the transition layer is located on a side of the conductive material layer close to the cross-linking layer to enhance the bonding force between the conductive material layer and the cross-linking layer.

[0020] In some embodiments, the material of the transition layer includes metal oxide.

[0021] In some embodiments, the composite current collector is a positive composite current collector, the conductive material layer includes aluminum, the longitudinal tensile strength MD of the positive composite current collector is ≥ 240 MPa, and the transverse tensile strength TD is ≥ 200 MPa; or,

[0022] The composite current collector is a negative electrode composite current collector, the conductive material layer includes copper, and the longitudinal tensile strength MD of the negative electrode composite current collector is ≥220 MPa, and the transverse tensile strength TD is ≥180 MPa.

[0023] In some embodiments, the composite current collector further includes a covering layer, wherein the covering layer is located on a side of the conductive material layer away from the polymer substrate.

[0024] In some embodiments, the conductive layer is symmetrically disposed on both sides of the polymer composite layer, wherein the cross-linked layer is symmetrically coated on both sides of the polymer substrate; the transition layer is symmetrically disposed on both sides of the cross-linked layer; and the conductive material layer is symmetrically disposed on both sides of the transition layer;

[0025] The covering layer is symmetrically arranged on both sides of the conductive layer.

[0026] In some embodiments, the thickness of the conductive layer is 0.11-1.6 μm, wherein the thickness of the transition layer is 0.01-0.1 μm, and the thickness of the conductive material layer is 0.1-1.5 μm.

[0027] In some embodiments, the bonding force between the polymer composite layer and the conductive layer is greater than or equal to 5.0 N / 15 mm and less than or equal to 10 N / 15 mm.

[0028] In some embodiments, the polymer substrate is a biaxially oriented polyethylene terephthalate (BOPET) film or a biaxially oriented polypropylene (BOPP) film.

[0029] According to a specific embodiment of the present disclosure, the present disclosure provides a composite pole piece, and the composite pole piece includes the composite current collector as described in any one of the above items.

[0030] According to a specific embodiment of the present disclosure, the present disclosure provides a lithium battery, including the composite pole piece as described above.

[0031] According to a specific embodiment of the present disclosure, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, comprising the following steps:

[0032] Step S1, preparing a polymer composite layer, comprises the following steps:

[0033] Step S11, providing a polymer substrate;

[0034] Step S12, at least a crosslinking agent, a stabilizer and a photoinitiator undergo a crosslinking polymerization reaction to obtain a crosslinked polymer, wherein the crosslinking agent is used to enhance the bonding force between the conductive layer and the polymer substrate, the stabilizer includes at least two types of reactants, and the stabilizer is used to enhance the thermal stability of the polymer substrate after the reaction;

[0035] Step S13, coating at least one surface of the polymer substrate with a cross-linked layer formed by a cross-linked polymer, wherein the cross-linked layer is used to enhance the thermal stability of the polymer substrate;

[0036] Step S2, providing a conductive layer on a side of the cross-linked layer away from the polymer substrate.

[0037] In some embodiments, the step S11 includes: providing a polymer substrate, and performing corona treatment on the polymer substrate.

[0038] In some embodiments, the step S12 includes: adding a stabilizer, a cross-linking agent, and a photoinitiator into a solvent, and stirring under closed conditions to obtain a modified cross-linked polymer.

[0039] In some embodiments, the step S13 includes: coating the cross-linked polymer on at least one surface of the polymer substrate, and irradiating with ultraviolet light for 15-60 seconds to form the cross-linked layer.

[0040] In some embodiments, step S2 includes:

[0041] Step S21, forming the metal oxide layer transition layer on at least one surface of the polymer composite layer by an in-situ reaction;

[0042] Step S22 , depositing a metal layer on a surface of the transition layer away from the cross-linking layer by physical vapor deposition, thereby forming a conductive material layer on the surface of the transition layer.

[0043] In some embodiments, after step S22, the method further includes: forming a covering layer on a surface of the conductive material layer away from the transition layer.

[0044] The embodiments of the present disclosure also provide a method for preparing a composite electrode, including any method for preparing a composite current collector as described above.

[0045] The embodiments of the present disclosure also provide a method for preparing a lithium battery, including any method for preparing a composite electrode as described above.

[0046] Compared with the prior art, the above solution of the embodiment of the present disclosure has at least the following beneficial effects:

[0047] The composite current collector provided by the present disclosure has a cross-linked layer arranged between the polymer substrate and the conductive layer. The cross-linked layer is a cross-linked polymer obtained by a cross-linking polymerization reaction of a stabilizer, a cross-linking agent and a photoinitiator. The cross-linked polymer has good thermal stability and can increase the heat resistance between the polymer substrate and the conductive layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0049] Figure 1 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0050] Figure 2 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0051] Figure 3 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0052] Figure 4 Schematic diagram of the cross-sectional structure of the composite current collector in some embodiments of the present disclosure.

[0053] The reference numerals in the specific implementation manner are as follows:

[0054] Composite current collector 10;

[0055] A polymer composite layer 1, a polymer substrate 11 and a cross-linking layer 12;

[0056] Conductive layer 2, transition layer 21, conductive material layer 22, covering layer 23. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.

[0059] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0060] In the description of the embodiments of the present invention, the orientations or positional relationships indicated by technical terms such as "upper", "lower", and "thickness" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present invention and simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present invention.

[0061] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0062] In the description of the embodiments of the present invention, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.

[0063] Reference to "embodiments" in this disclosure means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this disclosure may be combined with other embodiments.

[0064] See also Figure 1 The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer composite layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on at least one side of the polymer composite layer 1. The polymer composite layer 1 comprises a polymer substrate 11 and a cross-linking layer 12, wherein the cross-linking layer 12 is located on at least one surface of the polymer substrate 11, and the cross-linking layer 12 is located between the polymer substrate 11 and the conductive layer 2. The conductive layer 2 comprises a transition layer 21 and a conductive material layer 22, wherein the transition layer 21 is located on a side of the cross-linking layer 12 away from the polymer substrate 11, and the conductive material layer 22 is located on a side of the transition layer 21 away from the cross-linking layer 12.

[0065] The conductive layer 2 is located on at least one side of the polymer composite layer 1. In this embodiment, the conductive layer 2 is located on two opposite sides of the polymer composite layer 1. Figure 2 In some other embodiments, the conductive layer 2 may also be located only on one side of the polymer composite layer 1. When the conductive layer 2 is located on one side of the polymer composite layer 1, the cross-linked layer 12 is located on one surface of the polymer substrate 11, and the cross-linked layer 12 and the conductive layer 2 are located on the same side of the polymer substrate 11; when the conductive layer 2 is located on two opposite sides of the polymer composite layer 1, the cross-linked layer 12 is located on both surfaces of the polymer substrate 11.

[0066] The material of the polymer substrate 11 is preferably a polymer film. In some embodiments, the material of the polymer substrate 11 includes but is not limited to polyethylene (PE), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), biaxially oriented polyethylene terephthalate (BOPET), polyethylene terephthalate (PEN), poly (p-phenylene terephthalamide) (PPTA), polyimide (PI), polycarbonate (PC), polyetheretherketone (PEEK), polyoxymethylene (POM), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polyvinyl chloride (PVC), polyamide (PA) or polytetrafluoroethylene (PTFE) at least one. More preferably, when the composite current collector 10 is used as a positive electrode current collector, the polymer substrate 11 is a PET film or a BOPET film; when the composite current collector 10 is used as a negative electrode current collector, the polymer substrate 11 is a PP film or a BOPP film. Compared with PET film, BOPET film and BOPP film have better tensile strength, heat resistance, transparency, and are not easy to degrade compared with PP film, which is beneficial to improve the performance of composite current collector. PET is the preferred substrate because it is cheaper than PP, and has stronger tensile strength and heat resistance than PP. PET is the preferred positive electrode material because it has no degradation effect on positive electrode material aluminum. However, when used as a negative electrode substrate, PET is usually not suitable as a negative electrode substrate because copper can degrade PET, and PP is the preferred substrate for copper.

[0067] The cross-linked layer 12 is formed by coating a cross-linked polymer, and the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a stabilizer and a photoinitiator, wherein the cross-linking agent is used to enhance the bonding force between the conductive layer and the polymer substrate, and the stabilizer includes at least two reactants, and the stabilizer is used to enhance the thermal stability of the polymer substrate after the reaction. As mentioned above, for the negative electrode substrate, when copper is selected as the conductive material, PET cannot be selected as the substrate because the electrolyte may cause corrosion and degradation of PET. When PP is selected as the substrate, the heat resistance of PP is extremely poor. Therefore, by adding a stabilizer, the heat resistance of the PP substrate is enhanced, so that PP can be well used as the negative electrode substrate.

[0068] At least two reactants in the stabilizer are capable of undergoing polymerization reaction. The weight percentage of the stabilizer in the cross-linked polymer is preferably, but not limited to, 1%-10%, such as 2%, 5%, etc.

[0069] In some optional embodiments, the stabilizer includes acrylic acid or acrylic acid derivatives, and isocyanate or isocyanate derivatives. Isocyanate or isocyanate derivatives react with methylene succinic acid to produce polyurethane, which can improve the tensile properties of the cross-linked polymer, and the reaction of isocyanate or isocyanate derivatives with acrylic acid or acrylic acid derivatives can improve the thermal stability of the cross-linked polymer. Therefore, the cross-linked polymer generated by the reaction of acrylic acid or acrylic acid derivatives, isocyanate or isocyanate derivatives and methylene succinic acid can improve the mechanical properties of the polymer current collector 10, and improve the thermal stability of the polymer current collector 10, thereby increasing the service life of the battery.

[0070] The cross-linked layer 12 can also reduce the damage to the polymer substrate 11 during the sputtering of the transition layer 21 and the vacuum evaporation of the conductive material layer 22 during the preparation of the composite current collector 10. In addition, the cross-linked polymer of the cross-linked layer 12 has good thermal stability, which can increase the glass transition temperature of the polymer substrate 11, thereby improving the thermal stability of the polymer substrate; and the cross-linked polymer of the cross-linked layer 12 has good adhesion relative to the polymer substrate, which can increase the bonding force between the polymer substrate 11 and the conductive layer 2, and avoid the conductive layer 2 from falling off the polymer substrate 11 during use, thereby improving the conductivity and safety of the battery. Preferably, acrylic acid or acrylic acid derivatives account for 0.5%-5% of the cross-linked polymer by mass; isocyanate or isocyanate derivatives account for 0.5%-5% of the cross-linked polymer by mass. Isocyanate derivatives include, but are not limited to, alkyl monoisocyanates, (substituted) phenyl monoisocyanates, α-substituted benzyl isocyanates, polyisocyanates, phenylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), polymethylene polyphenyl polyisocyanate (PAPI) and hexamethylene diisocyanate (HDI).

[0071] Acrylic derivatives include, but are not limited to, at least one of acrylate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, glycidyl acrylate, and glycidyl methacrylate.

[0072] The cross-linking agent causes acrylic acid or acrylic acid derivatives to undergo cross-linking polymerization reaction with isocyanate or isocyanate derivatives to obtain a cross-linked polymer, thereby improving the adhesion of the cross-linked layer 12 and increasing the bonding force between the polymer substrate 11 and the conductive layer 2. The cross-linking agent includes but is not limited to methylene succinic acid, citraconic acid, mesaconic acid, 2-methylene succinic acid, succinic acid, etc. The mass percentage of the cross-linking agent to the cross-linked polymer is preferably, but not limited to, 1%-5%.

[0073] The photoinitiator includes but is not limited to diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenylacetone, 1-hydroxycyclohexylphenyl ketone, methyl benzoylformate, etc. Preferably, the mass percentage of the photoinitiator to the mass percentage of the crosslinker is 1%-5%.

[0074] The cross-linked polymer can be regulated by solid content and viscosity. The solid content is less than 5% and the viscosity is 100-300cp.

[0075] In this embodiment, the stabilizer 12 is a cross-linked polymer obtained by reacting acrylic acid, isocyanate, methylene succinic acid, and diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide.

[0076] The thickness of the polymer composite layer 1, the polymer substrate 11 and the cross-linking layer 12 can be selected according to actual conditions. In some preferred embodiments, the thickness of the polymer composite layer 1 is 2.1 to 13 μm, wherein the thickness of the polymer substrate 11 is 2 to 12 μm, and the thickness of the cross-linking layer 12 is 0.1 to 1 μm. The thickness of the cross-linking layer 12 is relatively small, and while increasing the bonding force between the polymer composite layer 1 and the conductive layer 2, the thermal stability of the polymer composite layer 1 and the mechanical properties of the polymer composite layer 1, the increase in the thickness and weight of the composite current collector 10 can be basically ignored. The thickness of the polymer composite layer 1 is in the micron level, thereby reducing the thickness and weight of the composite current collector 10.

[0077] The material of the transition layer 21 is not limited to metal oxides, and the metal oxide is preferably but not limited to AlO x In some embodiments, the transition layer 21 includes a metal oxide layer, and the metal oxide layer is formed on at least one surface of the polymer composite layer 1 by an in-situ reaction. The metal oxide layer serves as a transition layer between the metal conductive material 22 and the cross-linked layer 12, thereby enhancing the bonding force between the conductive material layer 22 and the cross-linked layer 12.

[0078] It can be understood that the transition layer 21 is an optional layer structure, see Figure 3 In some embodiments, the conductive layer 2 does not include the transition layer 21 , and the conductive material layer 22 is directly disposed on the surface of the cross-linked layer 12 away from the polymer substrate 11 .

[0079] The material of the conductive material layer 22 can be a metal or a carbon conductive material. Metals include but are not limited to aluminum, copper, nickel, titanium, silver, nickel-copper alloys, aluminum-zirconium alloys, and the like. Carbon conductive materials include but are not limited to carbon nanotubes, graphene, graphite, and the like. Preferably, the conductive material layer 22 is a metal layer. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, the conductive material layer 22 is metal aluminum, and the tensile strength of the composite current collector 10 is MD ≥ 240 MPa in the longitudinal direction and TD ≥ 200 MPa in the transverse direction. In other embodiments, the composite current collector 10 is used as a negative electrode current collector, the conductive material layer 22 is metal copper, and the tensile strength of the composite current collector 10 is MD ≥ 220 MPa in the longitudinal direction and TD ≥ 180 MPa in the transverse direction. Compared with existing current collectors, the tensile strength of the composite current collector 10 disclosed in the present invention is greatly improved.

[0080] See also Figure 4 In some optional embodiments, the side of the conductive material layer 22 away from the cross-linking layer 12 further includes a covering layer 23. The covering layer 23 can prevent the conductive material layer 22 from being oxidized, corroded or damaged. The material of the negative electrode covering layer 23 includes but is not limited to oxides such as copper oxide. The positive electrode is aluminum. Since the aluminum oxide protective layer can be generated by itself, there is no need to set a separate protective layer. Of course, an in-situ oxidation reaction can also be performed to actively generate the aluminum oxide protective layer.

[0081] The thickness of the conductive layer 2, the transition layer 21, the conductive material layer 22 and the covering layer 23 can be selected according to actual conditions. Preferably, the thickness of the conductive layer 2 is 0.11-1.6 μm, wherein the thickness of the transition layer 21 is 0.01-0.1 μm, and the thickness of the conductive material layer 22 is 0.1-1.5 μm. The thickness of the covering layer 23 is 0.01-1.4 μm. The thickness of the conductive layer 2 disclosed in the present invention is much smaller than the thickness of the conventional copper foil or aluminum foil current collector, thereby reducing the weight of the current collector and the battery, and increasing the energy density of the battery.

[0082] The bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 can reach 10N / 15mm. In some embodiments, the bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 is greater than or equal to 3.0N / 15mm and less than or equal to 10N / 15mm, which is much greater than the bonding force between the polymer substrate and the conductive layer in the existing composite current collector.

[0083] According to a specific embodiment of the present disclosure, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, comprising the following steps:

[0084] Step S1, preparing a polymer composite layer, comprises the following steps:

[0085] Step S11, providing a polymer substrate;

[0086] Step S12, at least a crosslinking agent, a stabilizer and a photoinitiator undergo a crosslinking polymerization reaction to obtain a crosslinked polymer, wherein the crosslinking agent is used to enhance the bonding force between the conductive layer and the polymer substrate, the stabilizer includes at least two types of reactants, and the stabilizer is used to enhance the thermal stability of the polymer substrate after the reaction;

[0087] Step S13, coating at least one surface of the polymer substrate with a cross-linked layer formed by a cross-linked polymer, wherein the cross-linked layer is used to enhance the thermal stability of the polymer substrate;

[0088] Step S2, providing a conductive layer on a side of the cross-linked layer away from the polymer substrate.

[0089] In some embodiments, the step S11 includes: providing a polymer substrate, and performing a corona treatment on the polymer substrate. The conditions of the corona treatment are selected according to the specific material of the polymer substrate 11. Preferably, the corona treatment is performed under 2800-3200W. In this embodiment, the polymer substrate 11 is a polymer film, and the polymer film is corona treated under 3000W to increase the surface energy of the polymer film, thereby increasing the adhesion of the cross-linked layer 12 on the surface of the polymer film.

[0090] In some embodiments, the step S12 includes: adding a stabilizer, a cross-linking agent, and a photoinitiator into a solvent, and stirring under closed conditions to obtain a modified cross-linked polymer.

[0091] In some embodiments, the step S13 includes: coating the cross-linked polymer on at least one surface of the polymer substrate, and irradiating with ultraviolet light for 15-60 seconds to form the cross-linked layer.

[0092] In some embodiments, step S2 includes:

[0093] Step S21, forming the metal oxide layer transition layer on at least one surface of the polymer composite layer by an in-situ reaction;

[0094] Step S22 , depositing a metal layer on a surface of the transition layer away from the cross-linking layer by physical vapor deposition, thereby forming a conductive material layer on the surface of the transition layer.

[0095] In some embodiments, after step S22, the method further includes: forming a covering layer on a surface of the conductive material layer away from the transition layer.

[0096] In some optional embodiments, the weight percentage of the stabilizer in the modified prepolymer is 1.0%-10%, the weight percentage of the crosslinker in the modified prepolymer is 1%-5%, and the weight percentage of the initiator in the crosslinker is 1%-5%. It is understood that the amount of the stabilizer, crosslinker and initiator is not limited to the above embodiments and can be adjusted according to actual conditions.

[0097] Preferably, the stabilizer includes acrylic acid or acrylic acid derivatives, and isocyanate or isocyanate derivatives, the mass percentage of acrylic acid or acrylic acid derivatives in the modified prepolymer is 0.5%-5%, and the mass percentage of isocyanate or isocyanate derivatives in the modified prepolymer is 0.5%-5%.

[0098] The solvent can be selected according to actual needs, as long as the cross-linking polymerization reaction can proceed. Preferably, the solvent is at least one of water or ethanol.

[0099] The stirring method can be selected according to actual conditions, such as ultrasonic stirring, electric stirring, mechanical stirring, etc. Preferably, ultrasonic stirring combined with mechanical stirring is used under closed conditions to uniformly mix acrylic acid or acrylic acid derivatives, isocyanate or isocyanate derivatives, crosslinking agent and initiator in the solvent.

[0100] In step S13, preferably but not limited to, a micro-gravure coater is used to uniformly coat the cross-linked polymer on at least one surface of the polymer substrate 11, and UV irradiation is performed at 1000W for a preset time for reaction curing, and the irradiation time is selected according to the specific material of the cross-linked polymer. Preferably, the reaction is cured at 15s-60s. The reaction curing time can be adjusted according to actual conditions. In some optional embodiments, the light reaction curing can be performed by segmented gradient illumination, for example, UV irradiation at 1000W for 20s, UV irradiation at 800W for 20s, and UV irradiation at 500W for 20s.

[0101] In some optional embodiments, the cross-linked layer 12 has a thickness of 0.1-1 μm.

[0102] In some optional embodiments, in step S2, providing the conductive layer 2 on the side of the cross-linked layer 12 away from the polymer substrate 11 includes: directly providing a conductive material layer 22 on the surface of the cross-linked layer 12 away from the polymer substrate 11. In some other optional embodiments, in step S2, providing the conductive layer 2 on the side of the cross-linked layer 12 away from the polymer substrate 11 includes: forming a transition layer 21 on at least one surface of the polymer composite layer 1, specifically, the transition layer 21 is a metal oxide layer, and the metal oxide layer is formed on at least one surface of the polymer composite layer 1 by in-situ reaction; then, forming a conductive material layer 22 on the surface of the transition layer 21 away from the cross-linked layer 12. Preferably, the conductive material layer 22 is a conductive metal layer, and the conductive material layer 22 is formed on the surface of the cross-linked layer 12 or the transition layer 21 away from the polymer substrate 11 by physical vapor deposition (PVD). More preferably, the conductive material layer 22 is formed on the surface of the cross-linked layer 12 or the transition layer 21 away from the polymer substrate 11 by evaporating metal. The evaporation method is preferably, but not limited to, resist evaporation, electron gun evaporation, etc.

[0103] In some optional embodiments, step S2 further includes the step of providing a covering layer 23 on the surface of the conductive material layer 22 away from the polymer substrate 11 .

[0104] According to experimental verification, the present application performs micro-gravure double-sided coating on a PET substrate with a width of 380 mm, a length of 300 m, and a thickness of 6 microns. The dry thickness of the AB surface coating is 300 nm. After measurement, the tensile strength MD of the substrate is increased from 297 MPa to 321 MPa, and the TD is increased from 254.7 MPa to 277 MPa. The elongation at break MD is reduced from 93.8% to 35.4%, and the TD is reduced from 110.2% to 51%.

[0105] According to some embodiments of the present disclosure, the present disclosure further provides a composite pole piece, comprising the composite current collector 10 provided by any of the above schemes or the composite current collector 10 obtained by the preparation method of the composite current collector provided by any of the schemes.

[0106] According to some embodiments of the present disclosure, the present disclosure further provides a lithium battery, comprising the composite pole piece provided by any of the above schemes.

[0107] According to some embodiments of the present disclosure, the present disclosure further provides a method for preparing a composite pole piece, including the method for preparing a composite current collector provided by any of the above schemes.

[0108] According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing a lithium battery, including a method for manufacturing a composite pole piece provided by any of the above schemes.

[0109] The composite current collector 10 and its preparation process and test data are introduced below through specific embodiments:

[0110] Embodiment 1:

[0111] In this embodiment, the polymer substrate 11 is a 6 μm thick PET film, and the cross-linking layer 12 is located on the upper and lower surfaces of the PET film. The cross-linking layer 12 includes a cross-linked polymer formed by the reaction of acrylic acid, isocyanate, methylene succinic acid, and diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide in ethyl acetate. The thickness of the cross-linking layer 12 is 0.5 μm. The transition layer 21 is a metal oxide AlO x The transition layer 21 is formed on the upper and lower surfaces of the cross-linked layer 12 away from the PET film by in-situ reaction, and the thickness of the transition layer 21 is 0.05 μm. The conductive material layer 22 is metal Al, and the thickness is 1.0 μm.

[0112] In this embodiment, the preparation method of the composite current collector specifically includes:

[0113] Step S1, performing corona treatment on the PET film under 3000W conditions; adding 5g of acrylic acid, 5g of isocyanate, 5g of methylene succinic acid and 5g of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide to ethyl acetate, performing ultrasonic and mechanical stirring under closed conditions, and stirring at 90°C for 0.5h to obtain a cross-linked polymer; using a micro-gravure coater to evenly coat the cross-linked polymer on the upper surface and the lower surface of the PET film, and then drying it under 1000W ultraviolet light for 40s to form a cross-linked layer on the upper surface and the lower surface of the PET film; and

[0114] AlO was sputtered on the cross-linked layers on both the upper and lower surfaces of the PET film. x , forming a transition layer; and vapor-depositing Al on the transition layer to obtain a composite current collector.

[0115] Embodiment 2:

[0116] The present embodiment 2 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a PET film with a thickness of 4.5 μm, and the conductive material layer 22 is metallic copper.

[0117] Embodiment 3:

[0118] The present embodiment 3 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a 4.5 μm thick BOPP film, and the conductive material layer 22 is metallic copper.

[0119] Comparative Example 1:

[0120] This comparative example is basically the same as Example 1, and the only difference is that the conductive layer of this comparative example is directly evaporated on the surface of the polymer substrate, and there is no cross-linking layer between the polymer substrate and the conductive layer.

[0121] Comparative Example 2:

[0122] Comparative Example 2 is substantially the same as Example 2, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0123] Comparative Example 3:

[0124] Comparative Example 3 is substantially the same as Example 3, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0125] Table 1 Comparison of composite current collector performance

[0126]

[0127] It can be seen from the performance comparison results of the composite current collector in Table 1 that the tensile strength of the composite current collector in Example 1 is 240MPa in the longitudinal direction, reaching 269MPa, and 200MPa in the transverse direction, reaching 224MPa, with strong tensile properties. The tensile strength of the composite current collector of Comparative Example 1 is 240≥MD≥200, which is 236MPa; 200≥TD≥180, which is 183MPa. This shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector. The strength of the modified substrate in Example 1 is also significantly greater than the strength of the substrate in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector substrate. The bonding force between the modified conductive layer and the substrate in Example 1 is also significantly greater than the bonding force in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the bonding force between the conductive layer and the substrate. The thermal shrinkage rate of the modified substrate in Example 1 is also significantly smaller than that of the substrate in Comparative Example 1, indicating that the modified layer in the composite current collector disclosed in the present invention greatly improves the thermal shrinkage rate of the substrate.

[0128] Table 2 Comparison of composite current collector core performance

[0129]

[0130] It can be seen from the performance comparison results of the composite current collector battery cells in Table 2 that the initial discharge capacity of Examples 1-3 of the present application is greater than the initial discharge capacity of the corresponding Comparative Examples 1-3, indicating that the composite current collector battery cells formed in each embodiment of the present application have good discharge performance.

[0131] The initial charge and discharge efficiency of Examples 1-3 of the present application is greater than that of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0132] The number of cycles of the capacity retention rate of Examples 1-3 of the present application is greater than the number of cycles of the capacity retention rate of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0133] The energy density of Examples 1-3 of the present application is greater than the energy density of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good safety performance.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them; although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A composite current collector, characterized in that: It comprises a polymer composite layer and a conductive layer, wherein the conductive layer is located on at least one side of the polymer composite layer. The polymer composite layer comprises a polymer substrate and a cross-linked layer, wherein the cross-linked layer is formed by coating a cross-linked polymer on at least one surface of the polymer substrate, and the cross-linked layer is located between the conductive layer and the polymer substrate, and the cross-linked layer is used to enhance the thermal stability of the polymer substrate; The cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a stabilizer and a photoinitiator. The cross-linking agent is used to enhance the bonding force between the conductive layer and the polymer substrate. The stabilizer includes at least two types of reactants and is used to enhance the thermal stability of the polymer substrate after the reaction.

2. The composite current collector according to claim 1, characterized in that: The stabilizer includes acrylic acid or acrylic acid derivatives, and isocyanate or isocyanate derivatives, wherein the reactant of isocyanate or isocyanate derivatives and the crosslinking agent is used to enhance the thermal stability of the polymer substrate.

3. The composite current collector according to claim 1, characterized in that: The stabilizer accounts for 1%-10% of the cross-linked polymer by mass.

4. The composite current collector according to claim 2, characterized in that: The mass percentage of the acrylic acid or acrylic acid derivatives in the cross-linked polymer is 0.5%-5%; and the mass percentage of the isocyanate or isocyanate derivatives in the cross-linked polymer is 0.5%-5%.

5. The composite current collector according to claim 1, characterized in that: The cross-linking agent includes at least one of the following: methylenesuccinic acid, citraconic acid, mesaconic acid, 2-methylenesuccinic acid or succinic acid.

6. A composite pole piece, characterized in that: The composite pole piece comprises the composite current collector according to any one of claims 1 to 5.

7. A lithium battery, characterized in that: Including the composite pole piece as described in claim 6.

8. A method for preparing the composite current collector according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, preparing a polymer composite layer, comprises the following steps: Step S11, providing a polymer substrate; Step S12, at least a crosslinking agent, a stabilizer and a photoinitiator undergo a crosslinking polymerization reaction to obtain a crosslinked polymer, wherein the crosslinking agent is used to enhance the bonding force between the conductive layer and the polymer substrate, the stabilizer includes at least two types of reactants, and the stabilizer is used to enhance the thermal stability of the polymer substrate after the reaction; Step S13, coating at least one surface of the polymer substrate with a cross-linked layer formed by a cross-linked polymer, wherein the cross-linked layer is used to enhance the thermal stability of the polymer substrate; Step S2, providing a conductive layer on a side of the cross-linked layer away from the polymer substrate.

9. A method for preparing a composite pole piece, characterized in that: A method for preparing the composite current collector according to claim 8.

10. A method for preparing a lithium battery, characterized in that: Including the method for preparing the composite pole piece as claimed in claim 9.